Disfungsi Penegakan Hukum Lingkungan dalam Kasus Limbah Peternakan Ayam di Madurejo Sleman - Wahid Hasyim Anna’im; Faik Muhammad; Aminah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the issue of the use of village treasury land in Madurejo, Sleman, which is used for chicken farming, causing environmental impacts such as strong odours, air pollution, and disturbance to residents' comfort. Although the contract for the use of village treasury land has expired and the village government has issued three warning letters to the farm owner, farming activities continue without strict law enforcement. This study uses a normative qualitative approach with analysis based on Lawrence M. Friedman's legal system theory, as well as reviewing the principles of ubi societas ibi ius and the philosophical, sociological, and juridical foundations in the formation of law. The results of the study show that the lack of law enforcement is caused by a weak legal structure (the indecisiveness of officials), the community's economic dependence on livestock farming, and a low culture of environmental law. The conclusion of this study confirms that the law has not functioned optimally as a means of ecological justice and social control. Therefore, consistent enforcement of environmental law, evaluation of village land management oriented towards sustainability, and increased public legal awareness are needed so that the law truly lives and protects shared ecological interests.